Fast multi‐parametric imaging in abdomen by B1+ corrected dual‐flip angle sequence with interleaved echo acquisition. Issue 5 (10th December 2021) - Peng, Hao; Cheng, Chuanli; Wan, Qian; Jia, Sen; Wang, Shuai; Lv, Jianxun; Liang, Dong; Liu, Wenzhong; Liu, Xin; Zheng, Hairong; Zou, Chao
Abstract: Purpose: To achieve simultaneous T 1, w /proton density fat fraction (PDFF)/ R 2 ∗ mapping in abdomen within a single breadth‐hold, and validate the accuracy using state‐of‐art measurement. Theory and Methods: An optimized multiple echo gradient echo (GRE) sequence with dual flip‐angle acquisition was used to realize simultaneous water T 1 ( T 1, w )/PDFF/ R 2 ∗ quantification. A new method, referred to as "solving the fat‐water ambiguity based on their T 1 difference" (SORT), was proposed to address the fat‐water separation problem. This method was based on the finding that compared to the true solution, the wrong (or aliased) solution to fat‐water separation problem showed extra dependency on the applied flip angle due to the T 1 difference between fat and water. The B 1 + measurement sequence was applied to correct the B 1 + inhomogeneity for T 1, w relaxometry. The 2D parallel imaging was incorporated to enable the acquisition within a single breath‐hold in abdomen. Results: The multi‐parametric quantification results of the proposed method were consistent with the results of reference methods in phantom experiments (PDFF quantification: R 2 = 0.993, mean error 0.73%; T 1, w quantification: R 2 = 0.999, mean error 4.3%; R 2 ∗ quantification: R 2 = 0.949, mean error 4.07 s −1 ). For volunteer studies, robust fat‐water separation was achieved without evident fat‐water swaps. Based on the accurate fat‐water separation, simultaneous T 1, w /PDFF/ R 2 ∗ quantification was realized for whole liver within a single breath‐hold. Conclusion: The proposed method accurately quantified T 1, w /PDFF/ R 2 ∗ for the whole liver within a single breath‐hold. This technique serves as a quantitative tool for disease management in patients with hepatic steatosis.